2023
DOI: 10.3390/su152316167
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Modeling (SEM) to Test Sustainable Development in University 4.0 in the Ultra-Smart Society Era

Joanna Rosak-Szyrocka,
Sunil Tiwari

Abstract: Sustainability has a significant role in the reputation and status of a higher education institution. Universities have a part in “forming the values of society” through educating the present and future generations of decision makers. Universities can help with economic and sustainable development (SD) in several ways, including mediating social conflicts and educating the public on scientific and technological issues. This study aimed to evaluate the students’ agreement level (as a latent construct) to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…It can, therefore, be concluded that the created hypothetical model confirms the fact that it is applicable in this form, as it shows a good degree of agreement with real data. This statement is confirmed also by values of other indicators: χ2 = 507.962, df = 468, p = 0.098, and it is in accordance with the theory presented in [40,43,47,60,61].…”
Section: The Model Of Cybersecuritysupporting
confidence: 88%
See 3 more Smart Citations
“…It can, therefore, be concluded that the created hypothetical model confirms the fact that it is applicable in this form, as it shows a good degree of agreement with real data. This statement is confirmed also by values of other indicators: χ2 = 507.962, df = 468, p = 0.098, and it is in accordance with the theory presented in [40,43,47,60,61].…”
Section: The Model Of Cybersecuritysupporting
confidence: 88%
“…Within this questionnaire, the basic pillars of CS threats and their sub-pillars were defined based on a brainstorming session of 15 specialists (more detailed in Section 2.2). The evaluation and analysis of the obtained data are based on the application of the structural equation modelling method (SEM) and confirmatory factor analysis [38][39][40][41][42][43][44][45][46][47]. Mathematical modelling using structural equations finds its application first in psychological research (in psychometrics), gradually the range of SEM applications expands marketing, strategic management, organizational research, management information systems, and operational management [38][39][40].…”
Section: The Problem Statement and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations